In silico rationalisation of selectivity and reactivity in Pd-catalysed C–H activation reactions - Cao, Liwei; Kabeshov, Mikhail; Ley, Steven V.; Lapkin, Alexei A. (Beilstein Journal of Organic Chemistry, 2020)
A computational approach has been developed to automatically generate and analyse the structures of the intermediates of palladium-catalysed carbon–hydrogen (C–H) activation reactions as well as to predict the final products. Implemented as a high-performance computing cluster tool, it has been shown to correctly choose the mechanism and rationalise regioselectivity of chosen examples from open literature reports. The developed methodology is capable of predicting reactivity of various substrates by differentiation between two major mechanisms – proton abstraction and electrophilic aromatic substitution. An attempt has been made to predict new C–H activation reactions. This methodology can also be used for the automated reaction planning, as well as a starting point for microkinetic modelling.
Keywords: C–H activation; density functional theory; reaction prediction

(untitled) - Grubbs, R. H.; Chang, S. (Tetrahedron, 1998)

(untitled) - Buchwald, S. L.; Mauger, C.; Mignani, G.; Scholz, U. (Adv. Synth. Catal., 2006)

(untitled) - Buitrago Santanilla, A.; Regalado, E. L.; Pereira, T.; Shevlin, M.; Bateman, K.; Campeau, L.-C.; Schneeweis, J.; Berritt, S.; Shi, Z.-C.; Nantermet, P.; Liu, Y.; Helmy, R.; et al. (Science, 2015)

(untitled) - Echtermeyer, A.; Amar, Y.; Zakrzewski, J.; Lapkin, A. (Beilstein J. Org. Chem., 2017)

(untitled) - Holmes, N.; Akien, G. R.; Blacker, A. J.; Woodward, R. L.; Meadows, R. E.; Bourne, R. A. (React. Chem. Eng., 2016)

(untitled) - Fitzpatrick, D. E.; Battilocchio, C.; Ley, S. V. (Org. Process Res. Dev., 2016)

(untitled) - Segler, M. H. S.; Waller, M. P. (Chem. – Eur. J., 2017)

(untitled) - Coley, C. W.; Jin, W.; Rogers, L.; Jamison, T. F.; Jaakkola, T. S.; Green, W. H.; Barzilay, R.; Jensen, K. F. (Chem. Sci., 2019)

(untitled) - Schwaller, P.; Gaudin, T.; Lányi, D.; Bekas, C.; Laino, T. (Chem. Sci., 2018)

(untitled) - Gao, H.; Struble, T. J.; Coley, C. W.; Wang, Y.; Green, W. H.; Jensen, K. F. (ACS Cent. Sci., 2018)

(untitled) - Korwar, S.; Burkholder, M.; Gilliland, S. E.; Brinkley, K.; Gupton, B. F.; Ellis, K. C. (Chem. Commun., 2017)

(untitled) - Roudesly, F.; Oble, J.; Poli, G. (J. Mol. Catal. A: Chem., 2017)

(untitled) - Chen, X.; Engle, K. M.; Wang, D.-H.; Yu, J.-Q. (Angew. Chem., Int. Ed., 2009)

(untitled) - McNally, A.; Haffemayer, B.; Collins, B. S. L.; Gaunt, M. J. (Nature, 2014)

(untitled) - Balcells, D.; Clot, E.; Eisenstein, O. (Chem. Rev., 2010)

(untitled) - Dedieu, A. (Chem. Rev., 2000)

(untitled) - Tomberg, A.; Muratore, M. É.; Johansson, M. J.; Terstiege, I.; Sköld, C.; Norrby, P.-O. (iScience, 2019)

(untitled) - Tomberg, A.; Johansson, M. J.; Norrby, P. O. (J. Org. Chem., 2018)

(untitled) - Valiev, M.; Bylaska, E. J.; Govind, N.; Kowalski, K.; Straatsma, T. P.; Van Dam, H. J. J.; Wang, D.; Nieplocha, J.; Apra, E.; Windus, T. L.; de Jong, W. A. (Comput. Phys. Commun., 2010)

(untitled) - Kabeshov, M. A.; Śliwiński, É.; Fitzpatrick, D. E.; Musio, B.; Newby, J. A.; Blaylock, W. D. W.; Ley, S. V. (Chem. Commun., 2015)

(untitled) - Krishnan, R.; Binkley, J. S.; Seeger, R.; Pople, J. A. (J. Chem. Phys., 1980)

(untitled) - Van Speybroeck, V.; Van Neck, D.; Waroquier, M.; Wauters, S.; Saeys, M.; Marin, G. B. (J. Phys. Chem. A, 2000)

(untitled) - Seregin, I. V.; Gevorgyan, V. (Chem. Soc. Rev., 2007)

(untitled) - Sommai, P.-A.; Tetsuya, S.; Yoshiki, K.; Masahiro, M.; Masakatsu, N. (Bull. Chem. Soc. Jpn., 1998)

(untitled) - García-Cuadrado, D.; de Mendoza, P.; Braga, A. A. C.; Maseras, F.; Echavarren, A. M. (J. Am. Chem. Soc., 2007)

Chemistry 14D thinkbook - Hardinger, S. (2005)

(untitled) - Hammond, G. S. (J. Am. Chem. Soc., 1955)

(untitled) - O'Boyle, N. M.; Banck, M.; James, C. A.; Morley, C.; Vandermeersch, T.; Hutchison, G. R. (J. Cheminf., 2011)

(untitled) - Chen, M.; Ren, Z.-H.; Wang, Y.-Y.; Guan, Z.-H. (J. Org. Chem., 2015)

(untitled) - Luo, S.; Luo, F.-X.; Zhang, X.-S.; Shi, Z.-J. (Angew. Chem., Int. Ed., 2013)

(untitled) - Xia, J.-B.; Wang, X.-Q.; You, S.-L. (J. Org. Chem., 2009)

(untitled) - Hossian, A.; Manna, M. K.; Manna, K.; Jana, R. (Org. Biomol. Chem., 2017)

(untitled) - Zhou, H.; Xu, Y.-H.; Chung, W.-J.; Loh, T.-P. (Angew. Chem., Int. Ed., 2009)

(untitled) - Jia, X.; Zhang, S.; Wang, W.; Luo, F.; Cheng, J. (Org. Lett., 2009)

(untitled) - Xu, B.; Liu, W.; Kuang, C. (Eur. J. Org. Chem., 2014)

(untitled) - Wu, J.; Lan, J.; Guo, S.; You, J. (Org. Lett., 2014)

(untitled) - Tani, S.; Uehara, T. N.; Yamaguchi, J.; Itami, K. (Chem. Sci., 2014)

(untitled) - Wang, S.; Liu, W.; Cen, J.; Liao, J.; Huang, J.; Zhan, H. (Tetrahedron Lett., 2014)

(untitled) - Zhang, F.; Greaney, M. F. (Angew. Chem., Int. Ed., 2010)

International Tables for Crystallography Volume C: Mathematical, physical and chemical tables - Orpen, A. G.; Brammer, L.; Allen, F. H.; Watson, D. G.; Taylor, R. (Typical interatomic distances: organometallic compounds and coordination complexes of the d- and f-block metals, 2004)

(untitled) - Wang, J.; Nie, Z.; Li, Y.; Tan, S.; Jiang, J.; Jiang, P.; Ding, Q. (J. Chem. Res., 2013)

(untitled) - Tian, Q.; He, P.; Kuang, C. (Org. Biomol. Chem., 2014)

(untitled) - Chan, C.-W.; Zhou, Z.; Yu, W.-Y. (Adv. Synth. Catal., 2011)

(untitled) - Banerjee, A.; Santra, S. K.; Guin, S.; Rout, S. K.; Patel, B. K. (Eur. J. Org. Chem., 2013)

(untitled) - Allu, S.; Swamy, K. C. K. (RSC Adv., 2015)

(untitled) - Giri, R.; Yu, J.-Q. (J. Am. Chem. Soc., 2008)